Investigate the Performance of Prussian White K2Fe[Fe(CN)6] Cathode for Potassium-Ion Battery - Luan, Van Hoang; Quynh, Do Ngoc Nhu; Le, Minh Vien; Dat, Ly; Dat, Nguyen Tan (Indonesian Journal of Chemistry, 2025)
In this report, potassium iron(II) hexacyanoferrate (KFHCF) was synthesized via a precipitation method under a nitrogen-controlled atmosphere, followed by a comprehensive evaluation of its electrochemical properties. Various characterization techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA) are employed to investigate the structural and morphological properties of the materials. The electrochemical performance of the KFHCF materials was systematically evaluated through galvanostatic discharge cycling and cyclic voltammetry (CV) measurements. The results reveal that KFHCF material synthesized with a 2:1 molar ratio between EDTA and free Fe2+ ions, dried under vacuum at 100 °C for 10 h, exhibits significantly enhanced electrochemical properties compared to those with a 1:1 molar ratio. The performance was further assessed using different electrolytes, specifically K2SO4 and KCl. The KFHCF-based electrode demonstrates a peak current density of nearly 4 mA cm−2 for the redox processes of both Fe(II) coordination sites in K2SO4 or KCl aqueous electrolyte at a scan rate of 10 mV s−1. Additionally, it delivers discharge capacities of 113.97 mAh g−1 (K2SO4) and 93.45 mAh g−1 (KCl) at current densities of 500 mA g−1. These findings underscore the promising potential of KFHCF as an efficient electrode material for electrochemical applications.